The perception of sacrum in modern architecture - Dmitruk, Michał (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2015)
Since the time of the first settlements and communities, people tend to believe in various deities. Along with the cultural and social development, religion has become codified and popularized amongst the growing number of believers, thus became an important factor in the social and political development. Growing importance of religious beliefs, resulted in organizing sacred spaces which later became churches and temples. Throughout the centuries, religion became a stimulant to unite and cooperate on the one hand, and a root of conflict and intolerance on the other. In present times, architects have to face a diversified beliefs and solve major cultural differences, while designing a contemporary temple. Nowadays designers have to create sacral architecture in a way providing peaceful coexistence and mutual respect between followers.